Service Quality as an Antecedent of Brand Equity: Empirical Evidence in the Medical Tourism from Jordan - Shriedeh, Fayez B.; Ghani, Noor Hasmini Abd. (International Review of Management and Marketing, 2017)
This study aims to investigate the effect of service quality on brand equity in medical tourism context. Service quality is considered as a critical success element for achieveing competitive advantage and building strong medical tourism brands in today's competitive market, Jordan is included. A brand with strong equity is vital weapon for a medical toursim's differentation strategy and development of customer loyalty. In this study, a survey has been distributed to 384 medical tourist's in Jordan. Only, 306 data are usable and were used for data analysis. The findings of this study showed that the service quality is significantly associated with overall brand equity. Also, each of service quality dimensions that referring to tangibility, reliability, responsiveness, empathy, and assurance are significantly correlated with overall brand equity. Keywords: Service quality, Brand equity, Medical tourism JEL Classifications: M31, M37, Z32